Implementation of Operational Management for MSME Business - Nasution, Winda Suci Lestari; Nusa, Patriot (Talenta Publisher, 2023)
The purpose of this writing is as a tool to find out what entrepreneurship means, because in a general sense, an entrepreneur is a person who carries out business activities that are characterized by intelligence or talent in recognizing new products, determining new production methods, arranging operations management for procuring new products, marketing them, as well as manage its operating capital. In addition to understanding the meaning of entrepreneurship, what must be owned by an entrepreneur in building his company. Then another goal is to find out what operational management is in the MSME business. Operational management itself has a meaning as a business area that focuses on the production process, as well as ensuring that maintenance and development take place effectively and efficiently. Operational management itself has the benefits and objectives of changing or transforming various resources owned by a large or small company, namely to organize and manage materials, production, inventory control, product quality control, and maintenance. Another purpose of this writing is to find out the operational management of the digital MSME business, namely INSOVIA. INSOVIA has implemented various operational management practices to build and develop its business in this digital era.